CompTIA CASP+ CAS-004 certification guide : develop CASP+ skills and learn all the key topics needed to prepare for the certification exam - Birch, Mark (Packt Publishing, 2023)
Architect, engineer, integrate, and implement security across increasingly complex, hybrid enterprise networks About This Audiobook Learn how to apply industry best practices and earn the CASP+ certification Explore over 400 CASP+ questions to test your understanding of key concepts and help you prepare for the exam Discover over 300 illustrations and diagrams that will assist you in understanding advanced CASP+ concepts In Detail CompTIA Advanced Security Practitioner (CASP+) ensures that security practitioners stay on top of the ever-changing security landscape. The CompTIA CASP+ CAS-004 Certification Guide offers complete, up-to-date coverage of the CompTIA CAS-004 exam so you can take it with confidence, fully equipped to pass on the first attempt. Written in a clear, succinct way with self-assessment questions, exam tips, and mock exams with detailed explanations, this audiobook covers security architecture, security operations, security engineering, cryptography, governance, risk, and compliance. You'll begin by developing the skills to architect, engineer, integrate, and implement secure solutions across complex environments to support a resilient enterprise. Moving on, you'll discover how to monitor and detect security incidents, implement incident response, and use automation to proactively support ongoing security operations. The audiobook also shows you how to apply security practices in the cloud, on-premises, to endpoints, and to mobile infrastructure. Finally, you'll understand the impact of governance, risk, and compliance requirements throughout the enterprise. By the end of this CASP study guide, you'll have covered everything you need to pass the CompTIA CASP+ CAS-004 certification exam and have a handy reference guide. Audience This CompTIA audiobook is for CASP+ CAS-004 exam candidates who want to achieve CASP+ certification to advance their career. Security architects, senior security engineers, SOC managers, security analysts, IT cybersecurity specialists/INFOSEC specialists, and cyber risk analysts will benefit from this book. Experience in an IT technical role or CompTIA Security+ certification or equivalent is assumed.